5G NR downlink AOD-based localization - Liang, Wenfei (Nanyang Technological University, 2022)
Large antenna arrays, millimeter-wave signals, large bandwidth and dense deployment are the characteristics of 5G networks. These technologies not only enable high-data rate communications but also have the potential superiority of accurate positioning. This dissertation aims to study the millimeter-wave positioning properties and existing angle of departure (AoD) based localization algorithms for 5G communication networks and integrate existing methods and add new contents to realize three-dimensional non-line-of-sight (NLOS) based localization with the assumption that received NLOS path signals only reflect once.